New species and new records of Calycomyza Hendel (Diptera: Agromyzidae) in Brazil - Monteiro, Nilton Juvencio Santiago; Esposito, Maria Cristina (Zootaxa, 2017)
Two new species and a new record of Calycomyza Hendel are described for the Brazilian Amazon: Calycomyza rolandrae sp. nov. and Calycomyza dryas sp. nov. This is the first time we recorded Calycomyza hyptisicola Spencer and Calycomyza richardsi (Spencer) in Brazil. These species can be distinguished by the structure of the male terminalia, but the female terminalia can be an important taxonomic character, especially the ninth abdominal sternite, ninth abdominal tergite and the marginal seta.